Comparison of Alemtuzumab Versus Basiliximab Induction Therapy in Elderly Kidney Transplant Recipients: A Single-Center Experience. (April 2021) - Yakubu, Idris; Ravichandran, Bharath; Sparkes, Tracy; Barth, Rolf N.; Haririan, Abdolreza; Masters, Brian
Background: The optimal choice of induction immunosuppression for elderly kidney transplant recipients remains unclear. Although alemtuzumab has been associated with escalating risk of death and graft loss in this population, this risk has not been adequately explored. The purpose of this study was to compare the safety and efficacy of alemtuzumab with basiliximab induction in this population. Methods: This is a retrospective matched cohort study of kidney transplant recipients aged ≥65 years. Patients who received alemtuzumab induction were matched (1:2) to a basiliximab control. The primary outcome was allograft survival. The incidence of acute rejection, infection, and all-cause mortality was measured. Results: Fifty-one and 102 patients were included in the alemtuzumab and basiliximab groups, respectively. Baseline demographics were similar between groups, except for more living donor transplant recipients in the alemtuzumab group (26/51 [51%] vs 31/102 [30.4%], P = .02). Acute cellular rejection occurred more frequently within the first year in the basiliximab group ( P = .02). There was no difference in rates of infection within the first year. Graft and patient survival rates were similar over the follow-up period. Patients receiving basiliximab had a higher glomerular filtration rate at 2 years posttransplant (59 mL/min/1.73 m 2 vs 49 mL/min/1.73 m 2, P = .03). Conclusions: Alemtuzumab induction is associated with similar outcomes to basiliximab in elderly kidney transplant recipients.